2021
DOI: 10.1136/bcr-2020-239963
|View full text |Cite
|
Sign up to set email alerts
|

Torsades de pointes in SARS-CoV-2 (COVID-19) pneumonia: medicine reconciliation and careful monitoring of QTc interval may help prevent cardiac complications

Abstract: Hydroxychloroquine has been widely prescribed to treat patients with COVID-19 pneumonia. A 73-year-0ld woman with COVID-19 pneumonia was treated with dexamethasone and hydroxychloroquine. Her home medications, citalopram and donepezil, were continued. The ECG prior to starting hydroxychloroquine showed normal sinus rhythm with prolonged corrected QT (QTc) of 497 ms, due to citalopram and donepezil therapy. Repeat ECG on days 3 and 4 of hydroxychloroquine therapy showed significantly prolonged QTc of 557 ms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Despite this, at its peak, more than 400 clinical trials testing hydroxychloroquine and chloroquine, alone or in combination with azithromycin, were recruiting for treatment of COVID‐19 (http://www.clinicaltrials.org), with many using doses several times higher than those recommended for their approved indications. Furthermore, while significant concern already existed around the cardiac safety profiles of each of these drugs (Chorin et al, 2020; Giudicessi et al, 2020; Rosenberg et al, 2020) and they were indeed linked with TdP in COVID‐19 patients (Aslam et al, 2021; Szekely et al, 2020), many factors associated with the pathophysiology of COVID‐19 might further increase proarrhythmic risk. For example, fever, electrolyte changes including hypokalaemia and hypermagnesaemia and systemic acidosis are common in COVID‐19 patients (Alfano et al, 2021; Lippi et al, 2020; Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, at its peak, more than 400 clinical trials testing hydroxychloroquine and chloroquine, alone or in combination with azithromycin, were recruiting for treatment of COVID‐19 (http://www.clinicaltrials.org), with many using doses several times higher than those recommended for their approved indications. Furthermore, while significant concern already existed around the cardiac safety profiles of each of these drugs (Chorin et al, 2020; Giudicessi et al, 2020; Rosenberg et al, 2020) and they were indeed linked with TdP in COVID‐19 patients (Aslam et al, 2021; Szekely et al, 2020), many factors associated with the pathophysiology of COVID‐19 might further increase proarrhythmic risk. For example, fever, electrolyte changes including hypokalaemia and hypermagnesaemia and systemic acidosis are common in COVID‐19 patients (Alfano et al, 2021; Lippi et al, 2020; Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 26 articles reporting cases related to the safety of HCQ or CQ during treatment for COVID-19 were found [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. Table 6 synthesises the data from the cases reporting HCQ and CQ adverse drug reactions in COVID-19-affected patients and Table S21 of Supplementary Material part 2 provides full details.…”
Section: Resultsmentioning
confidence: 99%
“…Cases of a complete heart block, an implanted pacemaker failure, and a QT-interval prolongation were described in patients treated with HCQ for autoimmune conditions [ 97 , 98 , 100 ], and cases of cardiovascular collapse, non-specified cardiac arrhythmia, and syncopal attacks with torsade de pointes were described in patients treated with CQ for malaria, amoebiasis, and a dermatological problem [ 95 , 96 , 99 ]. In patients being treated for COVID-19, six cases of cardiac adverse effects with QT interval prolongation were described, consisting of a case of QT interval prolongation and recurrent torsade de pointes with CQ [ 188 ], a case of right bundle branch block and critical QT interval prolongation with HCQ [ 181 ], a case of torsade de pointes in a patient treated with HCQ plus dexamethasone [ 190 ], a case of suspected HCQ-induced sinus bradycardia and QT interval prolongation [ 191 ], a case of QT prolongation in a patient treated with HCQ plus AZM [ 192 ], and a case of death due to progressive metabolic acidosis and multiple organ system failure in a patient being treated with HCQ plus AZM [ 186 ]. Additionally, a case of death from cardiac arrest in a patient who developed wide complex tachycardia during CQ plus AZM treatment [ 189 ], and a case of sinus bradycardia with HCQ plus AZM were reported [ 192 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of such considerations has been highlighted recently in relation to repurposing of drugs for treatment of COVID-19. Specifically, various combinations of drugs that are known to carry some degree of proarrhythmic risk, including chloroquine, hydroxychloroquine, azithromycin, erythromycin and lopinavir/ritanavir, have been proposed as potential therapies (Delaunois et al 2021 ; Zequn et al 2021 ) in COVID-19 patients where fever (Aslam et al 2021 ; Pan et al 2020 ; Zhou et al 2020 ), acidosis (Zhou et al 2020 ) and electrolyte disturbances (Alfano et al 2021 ; Lippi et al 2020 ; Stevens et al 2021 ) were also reported. Here, we will review both the clinical occurrence of diLQTS in the context of fever, hypokalaemia, hypomagnesemia and other electrolyte disturbances and the mechanisms by which these factors contribute to altered potency of hERG block and proarrhythmic risk.…”
Section: Drug-induced Long Qt Syndromementioning
confidence: 99%